Critical Success Factors for the Implementation of Enterprise Resource Planning Systems in Malaysia - Jafari, Seyed Mohammadbagher (2006)
Enterprise resource planning (ERP) systems as the last version of Manufacturing Resource Planning (MRP II) can be considered as the most important development in the corporate use of information technology and is beginning to be the backbone of organizations. The difficulties and high failure rate in implementing ERP systems have been widely cited in the literature. Factors affecting ERP implementation are complex and abundant. Numerous authors have identified a variety of factors that can be considered to be critical to the success of an ERP implementation.